THE SPEECH ACT IN KID OF 5 YEARS OLD - Sayyid Khairunas (Wanastra: Jurnal Bahasa dan Sastra, 2014)
In conveying something, the speaker indicates an action. Such measures can facilitate the speaker to make the listener know what the intent or desire of the speaker. This is referred to as a speech act. Speech acts can also be found in the speech of children aged 5 years. In delivering the speech, a person nconsciously produces certain actions that his/her wishes were conveyed through speech can be realized. This study intends to explain the forms of speech acts which are in children aged 5 yearswithin pragmatics study. The writer uses a speech ofthe child as the data of this study. Data collection was carried out either in the form of participation or just listento conversation of the child. The results showed that the form of speech acts which are used by5 years old kid are:directive, assertive, and expressive.The directive illocutionary act is mostly used. It indicates, in conveying meaning and intention, the 5 years old kid is already able to produce the indirect speech act. This shows that their cognitive has developed.